Continuous-wave terahertz quantum cascade laser based on a hybrid bound to bound quantum design - Li, Weijiang; Li, Yuanyuan; Ma, Yu; Xu, Yunfei; Liu, Junqi; Zhuo, Ning; Lu, Quanyong; Wang, Lijun; Zhang, Jinchuan; Zhai, Shenqiang; Liu, Shuman; Liu, Fengqi (Frontiers in Photonics, 2022)
We report a low threshold power density and high power output terahertz quantum cascade laser emitting at ~3.9 THz operating in continuous-wave mode. The high output power and wall-plug efficiency are achieved based on a hybrid bound-to-bound quantum active design. A record output power of 312 mW and a low threshold power density of 0.8 kW/mm3 in continuous-wave mode at 20 K is demonstrated for a 300-μm-wide and 2-mm-long single-ridge device. The highest wall-plug efficiency is 1.38% and the slope efficiency is 684 mW/A with an internal quantum efficiency of ~120 photons per injected electron. The demonstration of this low-threshold and high-power THz laser will promote THz-based remote sensing and standoff detection for pharmaceutical and health industry applications.